2021
DOI: 10.1002/pmrj.12533
|View full text |Cite
|
Sign up to set email alerts
|

Assessing Diagnostic and Severity Grading Accuracy of Ultrasound Measurements for Carpal Tunnel Syndrome Compared to Electrodiagnostics

Abstract: Background The combined sensory index (CSI) is the most sensitive electrodiagnostic criteria for carpal tunnel syndrome (CTS), and the CSI and Bland criteria have been shown to predict surgical treatment outcomes. The proposed ultrasound measurements have not been assessed against the CSI for diagnostic accuracy and grading of CTS severity. Objective To investigate the use of ultrasound evaluations for both diagnosis and assessment of severity grading of CTS in comparison to electrodiagnostic assessment. Desig… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
4
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 29 publications
(58 reference statements)
0
4
0
Order By: Relevance
“…In addition, we found that wrist movement also affected the median nerve position shift, and in patients with carpal tunnel syndrome, such position shift was also significantly reduced. This may be because carpal tunnel syndrome is often accompanied by chronic inflammatory hyperplasia of the synovium of the transverse carpal ligament and tendons, which can adhere to the perineurium, resulting in reduced movement and morphological changes of the median nerve [12]. This study found that compared with the control group, there were significant differences in the distance and crosssectional area between the proximal and distal ends of the median nerve in the mild, moderate, and severe groups.…”
mentioning
confidence: 68%
See 1 more Smart Citation
“…In addition, we found that wrist movement also affected the median nerve position shift, and in patients with carpal tunnel syndrome, such position shift was also significantly reduced. This may be because carpal tunnel syndrome is often accompanied by chronic inflammatory hyperplasia of the synovium of the transverse carpal ligament and tendons, which can adhere to the perineurium, resulting in reduced movement and morphological changes of the median nerve [12]. This study found that compared with the control group, there were significant differences in the distance and crosssectional area between the proximal and distal ends of the median nerve in the mild, moderate, and severe groups.…”
mentioning
confidence: 68%
“…In addition, we found that wrist movement also affected the median nerve position shift, and in patients with carpal tunnel syndrome, such position shift was also significantly reduced. This may be because carpal tunnel syndrome is often accompanied by chronic inflammatory hyperplasia of the synovium of the transverse carpal ligament and tendons, which can adhere to the perineurium, resulting in reduced movement and morphological changes of the median nerve [ 12 ].…”
Section: Discussionmentioning
confidence: 99%
“…The diagnostic tests evaluated and their weighted mean sensitivity and specificity are outlined in Tables 2 and 3. 16-128 Although studies utilizing “clinical diagnosis” as a reference standard were treated as a unified subset, many studies 16-128 were found to utilize different definitions of clinical diagnosis. An outline of the utilized definitions for “clinical diagnosis” is presented in Supplemental Digital Content 1.…”
Section: Resultsmentioning
confidence: 99%
“…USG had high diagnostic accuracy for CTS based on CSI criteria. However, it is unable to distinguish between CSI severity groups [ 6 ]. However, other reviews reported that USG is a reliable imaging modality to diagnose CTS [ 7 ].…”
Section: Introductionmentioning
confidence: 99%